2019
DOI: 10.1111/josh.12846
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Opportunities and Academic Outcomes of Fourth Grade Elementary School Students in Georgia

Abstract: BACKGROUND: Physical activity at schools is an important component in combatting childhood obesity. Studies have shown that physical activity at school is positively associated with academic outcomes. The purpose of this study is to examine associations between opportunity of physical activity time at school and academic outcomes. METHODS: This statewide, cross-sectional study utilized 2 data sources from the Georgia Department of Education andGeorgia Shape in 860 schools. Multivariable linear regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, for children with urban residence, the external environment may be unsuitable for engaging in outdoor sports, resulting in a decrease in their physical activity levels. At the same time, studies have shown that students with high SES have better academic performance ( 45 ), which implies more sitting time, which is detrimental to spine health.…”
Section: Discussionmentioning
confidence: 99%
“…However, for children with urban residence, the external environment may be unsuitable for engaging in outdoor sports, resulting in a decrease in their physical activity levels. At the same time, studies have shown that students with high SES have better academic performance ( 45 ), which implies more sitting time, which is detrimental to spine health.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that engaging in regular PA is closely related to good AA [29,30]. However, some studies have failed to find any type of relationship between these variables [31], and other works have even found an inverse relationship [32]. The distinct methodologies used to quantify both PA (considering intensity, duration, type, etc.)…”
Section: Physical Activity (Pa)mentioning
confidence: 99%
“…10 Conversely, individuals in urban areas with large number of streets had increased difficulty for children to participating in outdoor activities. 11 Despite documented geographic disparities in the availability of green spaces, there is no comprehensive study on the different PA environments that promote an active lifestyle and healthy weight and fitness among youth.…”
Section: Introductionmentioning
confidence: 99%